Rheology of Biological Soft Matter : Fundamentals and Applications - Kaneda, Isamu (Soft and Biological Matter,, 2017)
In this book, a wide range subjects in biorheology are dealt with, from fundamentals to applications. The inclusion of quite substantial chapters concerned with application aspects such as the latest studies on foods, cosmetics, personal care products, and biological tissues, related regenerative medicine, is one of the features of the book. For the fundamental aspects, studies on the physicochemical characteristics of biopolymer, the key substance of soft matter, are listed. By contrast, in the application aspect, although the main topic is the rheology of foods, focusing on the "texture" of mastication or swallowing, novel studies on cosmetics and personal care products concerning feeling during the lubrication by those products are also considered. This book will engage both a professional and an academic audience interested in soft matter, especially as related to food, cosmetics, and personal care products. In particular, this work will have a special appeal to scientists and engineers in the food and cosmetics industries and to graduate students preparing for those fields.